The Trait of Argument in The Students of Secondary Schools - Al-Fayyadh, Mohammed Ahmed; Kadhim Salman, Shuruq (Al-Adab Journal, 2021)
The present research tackles essential concepts in the individual’s character which are perseverance, it is one of the most motivating powers towards achievement; perseverant individuals are those with positive beliefs in their potentials and abilities that make them set their future plans that would lead them to the realization of their aspirations. Perseverance forms an important part in the lives of students that enables them to excel in their educational background and academic achievement in particular. The research aims at: Measuring perseverance feature in secondary school students Identifying the differences in perseverance according to gender and grade variants in secondary school students. To achieve the aforementioned aims, the researcher has chosen a sample of (400) female secondary school students in the capital Baghdad from the First Rasafa Directorate and Second Karkh Directorate who were randomly chosen according to the variables of gender and grade. The data is processed via the statistical tools. The present study has found that secondary school students have a statistically significant level of perseverance at the level (0,05), since there are no differences of statistical significance in perseverance according to gender variable and grade. And the findings were interpreted according to theories and models adopted and the research came up with a number of suggestions and recommendations.